Relationship between molar volume and rejection of arsenic species in groundwater by low-pressure nanofiltration process - Oh, JI; Lee, SH; Yamamoto, K (ELSEVIER, 2004)
Rejection of arsenite, dimethyl arsinic acid (DMAA), arsenate, chloride, nitrate and sulfate ion by low-pressure nanofiltration was evaluated by the extended Nernst-Planck model coupled with steric hindrance and Donnan equilibrium. The partition coefficient of K; for each solute was introduced to Donnan equilibrium. They could be obtained from the curve fitting with experimental rejection of solutes. In the case of anionic solutes such as H(2)ASO(3)(-), H2AsO4-, HAsO4-, (CH3)(2)AsO2-, NO3- and SO42-, the partition coefficient K-i was correlated with the molar volume. The empirical equation was obtained from the regression analysis between molar volume (V-A) and partition coefficient (Ki) of anionic solutes for ES10 (K-i = 3100V(A)(0.64)), NTR729HF (K-i = 930V(A)(0.44)) and NTR7250 (K-i = 1800V(A)(0.63)). The effective range of molar volume for the equation was from 0.5 x 10(-4) to 1.5 x 10(-4) m(3)/mol. The gradient value of the regression line of K-i with molar volume in log scale was closed to 2/3 for all membranes used. These results suggest that the interaction between anionic solute and membrane surface was affected mainly by the surface charge density corresponding to molar volume of ionic solute, although another factors need to be considered in order to account for a deviation from the 2/3. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: WATER